2006
DOI: 10.1097/01.hjr.0000194419.24261.5c
|View full text |Cite
|
Sign up to set email alerts
|

Soy products and risk of an aneurysmal rupture subarachnoid hemorrhage in Japan

Abstract: The findings suggest that a diet high in soy products may be protective against the development of subarachnoid hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Our methods were described previously in detail (Okamoto et al, 2001(Okamoto et al, , 2003Okamoto and Horisawa, 2006). Briefly, we recruited all consecutive and incident SAH patients admitted at two large medical hospitals located in Nagoya from April 1992 to March 1997.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our methods were described previously in detail (Okamoto et al, 2001(Okamoto et al, , 2003Okamoto and Horisawa, 2006). Briefly, we recruited all consecutive and incident SAH patients admitted at two large medical hospitals located in Nagoya from April 1992 to March 1997.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested that dietary antioxidants may play a protective role against the development of subarachnoid hemorrhage (SAH) (Marzatico et al, 1998;Leppala et al, 1999Leppala et al, , 2000Hirvonen et al, 2000;Kaynar et al, 2005;Okamoto, 2006;Okamoto and Horisawa, 2006). In general, various dietary antioxidants may be interactive or synergistic rather than isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Four case-control [6][7][8]10] and 3 cohort studies [5,9,12] presented results on dietary soy intake and stroke risk. As shown in figure 2 a, meta-analysis of cohort studies yielded an SRR of 0.92 (95% CI 0.70-1.10) for subjects in the highest category of soy consumption compared with those in the lowest category.…”
Section: Soy Consumption and Stroke Riskmentioning
confidence: 99%
“…However, findings from observational studies evaluating the possible beneficial effects of soy foods on CVD risk are not consistent [3][4][5][6][7][8][9][10][11][12][13] , and the data from these studies have not been systematically evaluated. Some studies provided evidence that soy products and foods significantly lowered the risk of stroke in men and women combined [8,10] or only in women [7,9] , whereas others observed no significant effect [5,6,12] . For the association between soy foods and risk of CHD, inconsistent results were observed [3-5, 7, 9, 11-13] .…”
mentioning
confidence: 99%
“…There is limited data upon which to make dietary recommendations specifically for the prevention of subarachnoid hemorrhage (SAH) in high-risk individuals [20,21,22,23,24,25,26,27]. There may be specific dietary exposure that alone or in association with the two established risk factors for the condition, namely hypertension and smoking, may contribute to the formation and rupture of intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%